2003
DOI: 10.1016/s0735-1097(03)00193-1
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic syndrome, diabetes, and subclinicalatherosclerosis assessed by coronary calcium

Abstract: Those with MetS or diabetes have an increased likelihood of CAC compared with those having neither condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(41 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…Other measures which more directly reflect atherosclerosis burden may be more important for further risk stratification of the patient with DM, such as coronary calcium which has been shown to add prognostic value in such patients. 1314 MetS, however, is a more heterogeneous condition associated with a wide variation in CVD risk, 26 with many persons at intermediate risk where further evaluation such as by echo LV mass, may be helpful for risk stratification; our data support this by showing a modest added value for echo LV mass in risk prediction in such persons and in those without MetS.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Other measures which more directly reflect atherosclerosis burden may be more important for further risk stratification of the patient with DM, such as coronary calcium which has been shown to add prognostic value in such patients. 1314 MetS, however, is a more heterogeneous condition associated with a wide variation in CVD risk, 26 with many persons at intermediate risk where further evaluation such as by echo LV mass, may be helpful for risk stratification; our data support this by showing a modest added value for echo LV mass in risk prediction in such persons and in those without MetS.…”
Section: Discussionsupporting
confidence: 64%
“…10 There is a need to better identify what further screening methods for subclinical CVD can further improve risk prediction in persons with MetS and DM. 11 For instance, it is known such persons demonstrate a greater extent of myocardial ischemia 12 and coronary calcium 13,14 , with the latter providing prognostic value for CVD events. 15 Whether subclinical CVD evidenced by higher LV mass provides significant incremental prognostic value in predicting CVD events over standard risk factors in these conditions is unclear, especially in those with MetS and DM and in older persons who have a longer exposure to these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Modified Asian ATP III criteria are the same as original ATP III except waist circumference (WC) greater than 90 cm in men and 80 cm in women [4]. Diagnosis requires having any three of five risk factors: abnormal WC, TG levels ≥150.0 mg/dL or pharmacologic treatment (Rx), HDL-C levels: <40.0 mg/dL in male and <50.0 mg/dL in female; or Rx, blood pressure: >130 mm Hg systolic and >85 mm Hg diastolic or Rx, and FBG concentration >100.0 mg/dL or Rx [11]. …”
Section: Methodsmentioning
confidence: 99%
“…DM has been evaluated by CAC in multiple studies, and the increased prevalence of CAC in DM is well documented, as is the worse prognosis in those with CAC. [3][4][5][6][7][8][9][10] In CCTA evaluations, Pundziute et al 9 noted more diseased segments, calcified and non-calcified plaques in 215 patients with symptomatic DM compared to individuals with no DM, and Scholte et al 10 in 70 patients with asymptomatic DM reported plaque in 80%, 41% of which were non-calcified. Neither paper evaluated patients with IFG.…”
Section: Discussionmentioning
confidence: 99%
“…1 To examine its relationship with clinical coronary artery disease (CAD), a systematic literature review of 18 studies reported a significant but modest relative risk of 1.18-1.20. 2 In the symptomatic and asymptomatic population, there are numerous studies documenting the increased association of DM with subclinical atherosclerosis, [3][4][5][6][7][8][9][10] but there are no data for pre-diabetes. Consequently, this study was designed to establish the role of IFG in plaque formation in asymptomatic patients compared to patients with DM and participants with normal fasting glucose (NFG), as measured by coronary computed tomographic angiography (CCTA).…”
mentioning
confidence: 99%